Underwater Drag Reduction Failure of Superhydrophobic Surface Caused by Adhering Spherical Air Bubbles - You Nie; Ding Weng; Jiadao Wang (Journal of Marine Science and Engineering)
Underwater drag reduction using superhydrophobic surfaces is a promising method due to its simplicity and low energy consumption. However, most attempts to obtain drag reduction using superhydrophobic surfaces have failed. Explanations such as air layer or air bubble vanishment and surface roughness are proposed in the existing works. In this work, the drag increase caused by spherical air bubbles adhering to the superhydrophobic surface is reported, and the drag increase mechanism is revealed by numerical simulation. In the water tunnel and towing tank experiment, we found that the experimental samples exhibited drag increase around a specific velocity, and the recorded optical images showed that the superhydrophobic surfaces were adhered by spherical air bubbles. Through numerical simulation, we found that the spherical air bubbles not only reduced the frictional drag but also introduced pressure drag. The drag increase was produced when the introduced pressure drag exceeded the reduced frictional drag. This work might be helpful for the drag reduction application of the superhydrophobic surface.